Potential of Photovoltaic Panels on Building Envelopes for Decentralized District Energy Systems - Middelhauve, Luise; Girardin, Luc; Baldi , Francesco; Maréchal, François (Frontiers in Energy Research, 2021)
The foreseen important increase of the penetration of distributed renewable energies technologies into the electricity distribution grid is expected to lead to some major challenges. As a main stakeholder, authorities often lack the appropriate tools to frame and encourage the transition, and monitor the impact of energy transition policies. This paper aims at combining a relatively detailed modelling of the PV generation potential on the building’s envelope while retaining the energy systems optimization approach. The problem was addressed as a multi-8objective, mixed integer-linear programming problem. Comparing to existing literature in the field, the proposed approach combines an advanced modelling of the energy generation potential from PV panels with a detailed representation of the district energy systems, thus allowing an accurate representation of the interaction between the energy generation from PV and the rest of the system. The proposed approach was applied to a typical, central European, residential district in Switzerland.The results of the application of the proposed method showed that the district can achieve carbon neutrality based on PV energy alone, but that this requires covering all the available district’s rooftops, and part of the district’s facades. Whereas facades are generally disregarded due to their lower generation potential, the results also allowed concluding that facade-PV can be economically convenient for a wide range of electricity prices, including those currently used by the Swiss grid operators. Achieving self-sufficiency at district scale is challenging: it can be achieved by covering approximately 42% to 100% of the available surface when the round trip efficiency decreases from 100% to 50%. The results underlined the importance of storage for achieving self-sufficiency: even with 100% round trip efficiency for the storage, very large capacities are required. However, energy demand reduction through renovation would allow to reach self-sufficiency (SS) with half of the PV and storage capacity required.